PLATFORM DIGITAL SEBAGAI ALTERNATIF BERTAHAN DI ERA PANDEMI COVID-19 BAGI PELAKU BISNIS PERTANIAN - Damara Dinda Nirmalasari Zebua; Lasmono Tri Sunaryanto (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
One of the vegetable and fruit shopping centers that affected by the Covid-19 pandemic is the Agro Store which is managed by the Hortimart Agro Center. This study aims to know: 1) the impact of the Covid-19 pandemic; 2) the use of the digital platform; and 3) the advantages of using digital platform. This is a descriptive qualitative research by using an interactive analysis model includes reduction, data presentation and conclusion drawing that used Altas.ti 8 as an analysis tool for data coding. The results of the study concludes: 1) the Covid-19 pandemic caused operational activities at the Agro Store to be closed for approximately four months; 2) the Whatsapp digital platform is an alternative platform for Agro Store to sell vegetable and fruit products online; and 3) internal constraints are the lack of human resources and transportation, while external constraints are complaints from customers. The implication of this research for Agro Store is a reminder and also a trigger to consistent use the digital platform as a marketing media of selling vegetable and fruit products online as an opportunity to expand the market and increase sales turnover.